Effects of detuning on control of intersubband quantum well transitions with chirped electromagnetic pulses - Blekos, K.; Simserides, C.; Terzis, A.F.; Paspalakis, E. (AIP Conference Proceedings, 2010)
We study the interaction of a chirped electromagnetic pulse with intersubband transitions of a double semiconductor quantum well. We specifically consider the interaction of the ground and first excited subbands with the electromagnetic field and use the nonlinear density matrix equations for the description of the system dynamics. These equations are solved numerically for various values of the electron sheet density for a realistic double GaAs/AlGaAs quantum well, and the efficiency of population transfer is discussed with emphasis given to the effects of the detuning of the central frequency of the electromagnetic field from resonance.